A novel green chemistry gelation method for polyvinyl pyrrolidone (PVP) and dimethylpolysiloxane (silicone): microwave-induced in-liquid-plasma. Issue 39 (12th July 2021) - Horikoshi, Satoshi; Sawada, Seiya; Serpone, Nick
Abstract : The discovery of a water-soluble polymer that cross-links to form a gel using a novel green gelation method: the microwave-induced in-liquid-plasma method that requires neither a cross-linking agent nor an initiator as are required in the conventional chemical method. Abstract : The focus of this article rests on our discovery that a water-soluble polymer could be cross-linked to form a gel using a novel Green Chemistry gelation method: the microwave-induced in-liquid-plasma (MILP) method that requires neither a cross-linking agent nor an initiator as are required in the conventional chemical method. For instance, the water-soluble polyvinyl pyrrolidone (PVP) polymer was gelled by MILP plasma irradiation within a few minutes without using toxic cross-linking agents and initiators. As well, the hydrophobic dimethylpolysiloxane macromolecule was dispersed in aqueous media to a colloidal sol, which could then also be easily gelled under MILP irradiation conditions within a few minutes, in comparison to the conventional method that often requires several hours to days for gelation to occur in the presence of cross-linking agents and initiators. The viscosity of the MILP silicone gel was greater than a similar gel formed by the conventional method. In contrast, the viscosity of the MILP-formed PVP gel was lower than the viscosity of the PVP gel obtained from the conventional method. Gels were characterized by 13 C-NMR spectrometry, FT-IR spectroscopy, SEM microscopy, viscosity measurements, and dynamic light scattering for particle size distributions. Plausible mechanistic stages for the two gelation occurrences have been inferred as involving the synergistic effects from microwaves, together with the sound waves (cavitation microbubbles), heat, UV and ˙OH radicals resulting from the microwave-generated in-liquid-plasma.